KOMPONEN MINYAK ATSIRI DARI DAUN TIGA JENIS TUMBUHAN FAMILI MYRTACEAE ASAL DESA SOA DAN DESA SOTA MERAUKE - Yuliasri Jamal; Chairul; Andria Agusta (The East Java Biological Society, 1997)
An isolation of the leaves of Asteromyrtus sp., Melaleuca leucaleucadendron, M. angustifolia and M. leucadendon Var. latifolia by steam distillation yielded 1.36, 1.02, 1.32 and 0.97 % essential oils respectively. Their constituents were analyzed using two combination techniques, gas chromathography and mass spectroscophy (GCMS). Based on their compositin, the essensial oils of Asteromyrtus sp., Melaleuca leucaleucadendron, M. angustifolia were considered acceptable for commercial essential oil production because of their potential source of cineole (65.11, 60.03. 82.43 % respectively), while M. leucadendon Var. latifolia was a very interesting source of methyleugenol (97.03%) which attractant activity.